Antibacterial activity of fingerroot (Boesenbergia rotunda) extract against acne-inducing bacteria - Rahman, Mohd Azuar Hamizan; Lau, Kah Yan; Rukayadi, Yaya (RJPBCS, 2016)
Fingerroot (Boesenbergia rotunda) is a medicinal and culinary herb in the ginger family (Zingiberaceae). It has been used for beauty and skin treatment, however, antibacterial activity of B. rotunda extract against acne-causing bacteria has not been investigated. The aim of this study is to analyse the antibacterial activity of B. rotunda extract acne-inducing bacteria; Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. The methanolic extract of B. rotunda was tested for antimicrobial activity against acne-causing bacteria in term of disk diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and kill-time curve using the standard methods of Clinical and Laboratory Standard Institute (CLSI). The B. rotunda extract has inhibited the growth of P. acnes ATCC6919, P. acnes clinical strain, S. epidermidis KCCM40003 and S. aureus KCCM12255 with MIC value of 0.63-, 0.63-, 0.31-, and 0.02 mg/mL, respectively. Moreover, MBC of B. rotunda extract was 1.25-, 1.25-, 0.63-, and 0.04 mg/mL on P. acnes ATCC6919, P. acnes clinical strain, S. epidermidis KCCM40003 and S. aureus KCCM12255, respectively. Time-kill curves analyses demonstrated that the bactericidal endpoint of B. rotunda extract on P. acnes ATCC6919, P. acnes clinical strain, and S. aureus KCCM12255 was 4× MIC after 4 h of incubation. Meanwhile, endpoint of B. rotunda extract on S. epidermidis was killed at 8×MIC after 0.5 h of incubation. The result show that B. rotunda extract have potent antibacterial activity against acne-inducing bacteria.